Conservation by Lending - Bård Harstad; Kjetil Storesletten (Center for Economic Studies and ifo Institute (CESifo), 2023)
This project analyzes how a principal can motivate an agent to conserve rather than exploit a depletable resource. This dynamic problem is relevant for tropical deforestation as well as for other environmental problems. It is shown that the smaller is the agent's discount factor (e.g., because of political instability), the more the principal benefits from debt-for-nature contracts compared to flow payments (in return for lower deforestation). The debt-for-nature contract combines a loan to the agent with repayments that are contingent on the forest cover.
Keywords: 330; environmental conservation; sovereign debt; sustainability-linked bonds; default; hyperbolic discounting; time inconsistency